Wrocławska fontanna Neptuna – przyczynek do dziejów i symboliki monumentu w świetle najnowszych odkryć - Sielicki, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
In 1732, the well in the middle of the Nowy Targ Square (before 1945 Neumarkt) in Wrocław (before 1945 Breslau) was replaced by an impressive Baroque fountain depicting Neptune, the Roman god of waters and seas. Over time, this artwork became part of local culture, traditions and customs. The figure of Neptune accompanied the trade in the square, New Year’s Eve parades and the Christmas market. In 1945, during the siege of the city, the surrounding buildings were mostly destroyed, together with the fountain.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne